Perbandingan Proses Sterilisasi Kalsium Karbonat (CaCO3) sebagai Bahan Baku Probiotik Hewan Berdasarkan Jumlah Total Sel Bakteri - Henny Parida Hutapea; Febriyanny Eka Setyowati (Universitas Sarjanawiyata Tamansiswa, 2023)
Calcium carbonate (CaCO3) is known as an inexpensive inorganic mineral commercially. Currently, calcium carbonate is widely used as a carrier for animal probiotics. As a carrier material, the use of calcium carbonate must be free from bacterial contamination. This is so that the probiotics production also do not contain bacteria other than the probiotics themselves. The method used was descriptive quantitative method. This study focused on examining the effectiveness of the calcium carbonate sterilization process with the dry sterilization process using an oven and the wet sterilization process using an autoclave based on the total plate count of bacteria. Based on the research, the normal treatment or without sterilization, Total Plate Count (TPC) calcium carbonate results were < 2.2 x 103 cfu/mL, in the wet sterilization treatment using an autoclave the total plate count was < 1.1 x 103 cfu/mL and the results in the sterilization treatment dry using an oven the total plate count was 0 colonies. The dry sterilization method using an oven is more suitable for calcium carbonate sterilization than the wet sterilization method using an autoclave. In the water content test, the same results were obtained for the three calcium carbonate treatments. This indicates that the dry and wet sterilization methods for calcium carbonate did not affect the percentage of water content contained therein. In the pathogen test, negative results were obtained for Escherichia coli and Salmonella sp in all three treatments.